2015
DOI: 10.1371/journal.pone.0117497
|View full text |Cite
|
Sign up to set email alerts
|

Therapy with Plasma Purified Alpha1-Antitrypsin (Prolastin®) Induces Time-Dependent Changes in Plasma Levels of MMP-9 and MPO

Abstract: The common Z mutation (Glu342Lys) of α1-antitrypsin (A1AT) results in the polymerization and intracellular retention of A1AT protein. The concomitant deficiency of functional A1AT predisposes PiZZ subjects to early onset emphysema. Clinical studies have implied that, among the biomarkers associated with emphysema, matrix metalloproteinase 9 (MMP-9) is of particular importance. Increased plasma MMP-9 levels are proposed to predict the decline of lung function as well as greater COPD exacerbations in A1AT defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 55 publications
0
9
0
Order By: Relevance
“…In support of this hypothesis, excessive neutrophil infiltration into the lung correlates with increased MMP-9 production ( Narasaraju et al, 2011 ), and MMP-9 was suggested as a biomarker to predict decline of lung function in patients with AATD ( Omachi et al, 2011 ). By contrast, serum MMP-9 levels seem to be lower in AATD patients receiving AAT therapy than in those without it ( Koepke et al, 2015 ).…”
Section: Aat As An Inhibitor Of Neutrophil Non-serine Proteasesmentioning
confidence: 99%
“…In support of this hypothesis, excessive neutrophil infiltration into the lung correlates with increased MMP-9 production ( Narasaraju et al, 2011 ), and MMP-9 was suggested as a biomarker to predict decline of lung function in patients with AATD ( Omachi et al, 2011 ). By contrast, serum MMP-9 levels seem to be lower in AATD patients receiving AAT therapy than in those without it ( Koepke et al, 2015 ).…”
Section: Aat As An Inhibitor Of Neutrophil Non-serine Proteasesmentioning
confidence: 99%
“…Interestingly, proteases outside the serine-protease family are also inhibited by hAAT, albeit to a lesser extent. These include metalloproteases [e.g., MMP-9 ( 15 17 ), ADAMTS-4 ( 18 ), and cysteine-proteases (e.g., caspase-3) ( 19 , 20 )], suggesting that some functions of the molecule may extend beyond the specificity conferred by the primary sequence of the RCL. As such, it has been proposed that the globular surface of hAAT may contain significant functional attributes.…”
Section: Introductionmentioning
confidence: 99%
“…Concentration of total MMP-9 (human MMP-9 assay measures the 92 kDa Pro-MMP-9 and the 82 kDa active MMP-9) was detected by the immune/sandwich ELISA method according to the kit procedure (Human MMP-9, R&D Systems). The method is based on the measurement of total MMP-9 amount, the enzyme included in degradation of extracellular matrix which could be in active form or preform 27 . After determination, the total protein concentration, supernatants of peritumoral and carcinoma tissue were used as the samples for the total MMP-9 concentration.…”
Section: Determination Of Metalloproteinases 9 Concentration (Mmp-9)mentioning
confidence: 99%